Clinical cancer research: The past, present and the future - Devita, V; Eggermont, A; Hellman, S; Kerr, D (Nature Publishing Group, 2014)
In the past decade, we have witnessed unprecedented changes and some remarkable advances that have enabled true personalized medicine. Nevertheless, many challenges in clinical cancer research remain and need to be overcome if we are to witness similar progress in the next decade. Such hurdles include, but are not limited to, clinical development and testing of multiple agents in combination, design of clinical trials to best accommodate the ever increasing knowledge of heterogeneity of the disease, regulatory challenges relating to drug development and trial design, and funding for basic research. With this in mind, we asked four leading cancer researchers from around the world, and who have been associated with the journal since its launch in November 2004 what, in their opinion, we have learnt over the past 10 years and how we should progress in the next 10 years.